Pemphigus Vulgaris and Pemphigus Foliaceus: Differences in Epidemiology and Mortality - Khalaf Kridin (Acta Dermato-Venereologica, 2017)

(untitled)
Little is known about differences in epidemiological features and prognosis between pemphigus vulgaris (PV) and pemphigus foliaceus (PF). The objective of this study was to compare PV and PF patients regarding ethnic variations and mortality rates. Mortality of PV and PF patients was compared with age- and sex-matched control subjects in the general population. The study cohort comprised 207 patients with PV and 30 with PF diagnosed during the period 2000 to 2015. The incidence rate of PV among Jews was 3.6-fold higher than among Arabs (p < 0.001), whereas no ethnic predisposition to PF was noted (p = 0.379). The risk of death for patients with PV was almost 3-fold higher than in the general population (standardized mortality ratio (SMR) 2.6). For patients with PF, the risk of mortality was not significantly increased relative to the general population (SMR 1.4). There is a racial predisposition to PV, whereas PF is sporadic. Mortality among patients with PV is higher compared with PF and the general population.